Cover Image. Issue 2 (21st February 2023) - Qiao, Yao; Fring, Lisa D.; Pallaka, Madhusudhan R.; Simmons, Kevin L.
Abstract : Cover Image: The cover image is based on the Review Article A review of the fabrication methods and mechanical behavior of continuous thermoplastic polymer fiber–thermoplastic polymer matrix composites by Yao Qiao et al., https://doi.org/10.1002/pc.27139 .